Good evidence on measurement properties of the dermatology life quality index, itchy quality of life and 5-dimensions itch scales in atopic eczema, but problems with structural validity remain - Apfelbacher, Christian; Ofenloch, Robert (British journal of dermatology, 2019)
Linked Article: Patel et al. Br J Dermatol 2019; 180:1083-1089.